REVIEW ARTICLE: AYURVEDIC PERSPECTIVE OF PRIMARY DYSMENORRHOEA - Rajini P; Maya Balakrishnan (International Journal of Applied Ayurved Research, 2021)
Dysmenorrhoea is a gynaecological disorder where there is cramping pain associated with menstruation. This is estimated to occur in 20-90% of women of reproductive age. Primary dysmenorrhoea refers to painful periods without pelvic pathology which usually begins around the onset of menstruation & lasts less than three days which is widely prevelant. Among yonirogas pain associated with menstruation is considered as a symptom in many diseases like vatiki, udavarta, paripluta, sannipathiki yoni vyapath etc . In this article, by referring available ayurvedic classical texts & modern literature an attempt to correlate primary dysmenorrhoea & udavartha is done. Eventhough there are no direct correlations about primary dysmenorhoea, among vimsathi yonirogas, udavarta yoni vyapad is a condition which presents with similar etiopathogenesis and clinical features. While describing the features of udavarta, Caraka says that “artave sa vimukthe tu tat kshanam labhate sukham” which implies an immediate relief of pain following the discharge of menstrual blood, which clearly denotes spasmodic type of dysmenorrhoea. On conclusion Udavarta yonivyapath can be considered as Primary Dysmenorrhoea explained in modern texts.